Equilíbrio líquido-líquido de sistemas aquosos com tensoativos polietoxilados: dados experimentais e modelagem - Araújo, Alessandro Alisson de Lemos (2013)
The nonionic surfactants when in aqueous solution, have the property of separating into two phases, one called diluted phase, with low concentration of surfactant, and the other one rich in surfactants called coacervate. The application of this kind of surfactant in extraction processes from aqueous solutions has been increasing over time, which implies the need for knowledge of the thermodynamic properties of these surfactants. In this study were determined the cloud point of polyethoxylated surfactants from nonilphenolpolietoxylated family (9,5 , 10 , 11, 12 and 13), the family from octilphenolpolietoxylated (10 e 11) and polyethoxylated lauryl alcohol (6 , 7, 8 and 9) varying the degree of ethoxylation. The method used to determine the cloud point was the observation of the turbidity of the solution heating to a ramp of 0.1 ° C / minute and for the pressure studies was used a cell high-pressure maximum ( 300 bar). Through the experimental data of the studied surfactants were used to the Flory - Huggins models, UNIQUAC and NRTL to describe the curves of cloud point, and it was studied the influence of NaCl concentration and pressure of the systems in the cloud point. This last parameter is important for the processes of oil recovery in which surfactant in solution are used in high pressures. While the effect of NaCl allows obtaining cloud points for temperatures closer to the room temperature, it is possible to use in processes without temperature control. The numerical method used to adjust the parameters was the Levenberg - Marquardt. For the model Flory- Huggins parameter settings were determined as enthalpy of the mixing, mixing entropy and the number of aggregations. For the UNIQUAC and NRTL models were adjusted interaction parameters aij using a quadratic dependence with temperature. The parameters obtained had good adjust to the experimental data RSMD < 0.3 %. The results showed that both, ethoxylation degree and pressure increase the cloudy points, whereas the NaCl decrease